Pengaruh Profitability, Growth, Tangibility, Dividend Policy Dan Fcf Terhadap Debt Policy - Clara, Tony Sudirgo (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
This study aims to obtain empirical evidence on the influence of profitability, growth, tangibility, dividend policy and free cash flow on the value of companies’ debt policy in manufacturing companies listed on the Indonesia Stock Exchange during 2014-2016. Tests using purposive sampling with SPSS ver 23.0. The number of samples used in this study were 114 samples. T test shows that profitability and free cash flow have positive and unsignificant effect, growth and dividend policy have negative and unsignificant effect, and tangibility has positive and significant influence on debt policy. The result of F test is profitability, growth, tangibility, dividend policy and free cash flow have simultant significant influence on debt policy.